Tumors in the setting of dupilumab use: A review of the literature - Shumeng Guo; Liangchun Wang, MD, PhD; Dingfang Bu, MD, PhD; Fengjie Liu, MD, PhD (World Allergy Organization Journal)
Dupilumab is the first monoclonal antibody approved for treating moderate-to-severe atopic dermatitis (AD) and has significantly improved the quality of life of AD patients. However, the safety of dupilumab is yet unclear in the context of cancer. Therefore, we aimed to investigate the safety of dupilumab and its relationship with the progression and occurrence of tumors. By reviewing relevant medical records of 90 patients who had pre-existing tumors before dupilumab treatment or presented new tumors after dupilumab treatment, we found that dupilumab probably had no significant negative effects on most tumors, but several patients with Cutaneous T-cell lymphomas (CTCLs) had relatively unfavorable outcomes during dupilumab treatment. Besides, CTCLs and lymphomas accounted for the majority of patients who presented new tumors after dupilumab treatment. Several patients were first diagnosed with presumed AD and probably were the presentations of CTCL at an early stage, and they developed typical CTCL symptoms after dupilumab treatment. Finally we came to the conclusion that dupilumab is safe for most patients with cancer. However, the effect of dupilumab on CTCLs is disputable. The use of dupilumab requires individual evaluation and closely monitored. When the efficacy is poor, re-evaluation of the diagnosis, especially of CTCLs and related diseases, is necessary.